2014
DOI: 10.5755/j01.ee.25.4.5263
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hysteresis in Unemployment Rates with Structural Breaks: the Case of Selected European Countries

Abstract: In recent years, unemployment has become a major problem in many countries. The fluctuations of the unemployment rate as well as its persistence in some countries impose challenges to economic policy makers. In order to implement appropriate policy measures, it is necessary to know the exact character of the unemployment in the observed countryis it structural or cyclical. In the context of economic theory, it is important to examine which concept better represents the behaviour of the unemployment ratesthe co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Marjanovic and Mihajlovic (2014) argue that structural break tests are the most widely used method to detect hysteresis. In this sense, structural break tests have been used in pioneering studies in the hysteresis literature (Baldwin, 1988; Blanchard & Summers, 1986; Mitchell, 1993; Røed, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marjanovic and Mihajlovic (2014) argue that structural break tests are the most widely used method to detect hysteresis. In this sense, structural break tests have been used in pioneering studies in the hysteresis literature (Baldwin, 1988; Blanchard & Summers, 1986; Mitchell, 1993; Røed, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Smooth transition structural break periods, on the other hand, occurred in 2014Q4 in investments, 2013Q3 in interest rates, 2012Q3 in GDP, and 2012Q3 in productivity. Marjanovic and Mihajlovic (2014) argue that structural break tests are the most widely used method to detect hysteresis. In this sense, structural break tests have been used in pioneering studies in the hysteresis literature (Baldwin, 1988;Blanchard & Summers, 1986;Mitchell, 1993;Røed, 1997).…”
Section: Smooth Transitions Structural Break Unit Root Testmentioning
confidence: 99%
“…Based on the simple fact, that unemployment rate is a nonstationary variable, Marjanovic and Mihajlovic concluded that time independent natural rate does not exist and it changes with almost every change in the unemployment rate (Marjanovic et al, 2014). This conclusion follows from the knowledge that non-stationary variables do not have constant and time independent means.…”
Section: An Overview Of Previous Studies About the Phillips Curve Rel...mentioning
confidence: 99%
“…Gohmann and Fernandez (2014 apply a panel vector autoregressive model, determining the causal relationship between unemployment and ownership in the U.S. states using the 1976-2009 data. Marjanovic and Mihajlovic (2014) examine the presence of hysteresis in monthly unemployment rates in selected European OECD states and transition countries of Central and Eastern Europe in the 2000-2013 period, structural analysis suggesting that the hysteresis hypothesis can be rejected in the case of OECD countries, unlike the latter ones.…”
Section: Introductionmentioning
confidence: 99%